Landscape impacts on pollinator communities in temperate systems: evidence and knowledge gaps. (19th December 2016) - Senapathi, Deepa; Goddard, Mark A.; Kunin, William E.; Baldock, Katherine C. R.
Summary: This review assesses current knowledge about the interplay between landscape and pollinator communities. Our primary aim is to provide an evidence base, identify key gaps in knowledge and highlight initiatives that will help develop and improve strategies for pollinator conservation. Human‐dominated landscapes (such as arable land and urban environments) can have detrimental impacts on pollinator communities but these negative effects can be ameliorated by proximity to semi‐natural habitat and habitat corridors. There is also evidence to suggest that increased landscape heterogeneity and landscape configuration can play an important role in the maintenance of diverse pollinator communities. Landscape characteristics have direct impacts on pollinator communities, but can also influence abundance and richness through interaction with other drivers such as changing climate or increased chemical inputs in land management. The majority of existing literature focuses on specific hymenopteran groups, but there is a lack of information on the impact of landscape changes on non‐bee taxa. Research is also needed on the effectiveness of management interventions for pollinators and multiple year observations are required for both urban and rural initiatives. Current policies and monitoring schemes could contribute data that will plug gaps in knowledge, thus enabling greater understanding of relationships between landscapes and pollinator populations. This would in turn help design mitigation and adaptation strategies for pollinator conservation. A lay summary is available for this article. Abstract : Lay Summary